The concentration of potentially toxic elements (PTEs) in honey: A global systematic review and meta-analysis and risk assessment. (September 2019) - Fakhri, Yadolah; Abtahi, Mehrnoush; Atamaleki, Ali; Raoofi, Amir; Atabati, Hamid; Asadi, Anvar; Miri, Ali; Shamloo, Ehsan; Alinejad, Abdolazim; Keramati, Hassan; Mousavi Khaneghah, Amin
Abstract: Background: However, the consumption of honey offers several beneficial advantages; it can be sources of some contaminants, such as potentially toxic elements (PTEs). Scope and approach: In the current study, the related investigations regarding the concentration of PTEs in honey a global scale among the international databases including Scopus, PubMed, ISI Web of Science and Embase were collected and analyzed. Also, the health risk assessment in the children and adults due to ingestion of PTEs via consumption honey was estimated by calculating hazard quotient (HQ) and total hazard quotient (THQ) and cancer risk (CR). Key findings and conclusions: Meta-analysis of 33 articles with 45 studies indicates that the overall rank order of PTEs according to their pooled concentration PTEs can be summarized as Fe (5.657 mg-kg-DW) > Mn (3.430 mg-kg-DW) > Pb (0.555 mg-kg-DW) > Cr (0.496 mg-kg-DW) > Cu (0.330 mg-kg-DW) > Ni (0.312 mg-kg-DW) > Cd (0.049 mg-kg-DW) > As (0.026 mg-kg-DW) > Hg (0.002 mg-kg-DW). The rank order of PTEs according to HQ was defined as Pb > Cd > Mn > Fe > Ni > As > Cu > Hg > Cr. Moreover, the lowest and highest values of HQ were observed in Macedonia and Turkey, respectively. The corresponded values of HQ and THQ in all countries investigated was lower than 1 value. Therefore, consumers are not at non-carcinogenic risk. Also, CR inorganic of As in the consumers in all countries investigated was lower than <1.00E-06 value. Hence, consumers are not at significant carcinogenic risk. Graphical abstract: Image 1